ASSESSMENT OF KNOWLEDGE AND AWARENESS ABOUT RADIATION SAFETY PROTOCOL AMONG DENTAL PRACTITIONERS IN CHENNAI - WILSON, DR. MARIA PRISCILLA WINCY; FRANKLIN, DR. CATHERINE; RAMAKRISHNAN, DR. SANKAR NARAYANAN; R, TEJASVI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Radiographs are commonly taken during dental diagnosis and treatment. Patients, and dental practitioners potentially receive exposure. Though it is considered that only a negligible radiation dose occurs during dental radiography, frequent and long-term exposure to this negligible radiation dose should not be ignored. Aim: To assess the knowledge and awareness about radiation techniques, biological impacts, and safety procedures. Materials and method: A Cross sectional survey with 20 closed ended questions was conducted on 200 Dental practitioners in Chennai. Results: Out of 200 participants, 45.5% had very poor awareness of radiation safety protocols, 23% had moderate awareness and 31.5% had very good awareness. Conclusion: Our study results conclude that most of the respondents have fair fundamental knowledge and awareness of radiation and protection, but with varying degrees. This reveals the need for more lectures and seminar programs for dental practitioners and during college years. This will result in a significant improvement in understanding for observing dental radiography's fundamental principles.